If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(21y) = 0 Remove parenthesis around (21y) -2 * 21y = 0 Multiply -2 * 21 -42y = 0 Solving -42y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-42'. y = 0 Simplifying y = 0
| 4(6t+2)=53 | | 4(6t+2)=60 | | -2x=-2+8 | | 5x-6=-81 | | 4(6t+2)=4 | | 5x+12-9x=19-15x+11x-7 | | 7x-6x+4x-9x= | | 9+8q=11+7q | | 4(6t+2)=50 | | 4(6t+2)=40 | | 4(6t+2)=28 | | -22(a+6)=-22 | | -3x-2=25 | | 5d-32=8 | | 4r-(-11)=87 | | x/3+4=-2 | | x^4-5x^2-36= | | 10+2(2x-3)=17-(3x-8) | | 3y+78= | | (2x+9)(x+8)=0 | | 8d-22=52 | | 2s+4.6=3s-1.2 | | 5x-32=43 | | 3(m+10)= | | 7x^2=73 | | -5600+200x=0 | | -7(z+4)+3z= | | g-0+4g+6=12 | | 2x*1=x+4 | | -x^2+18x-65=0 | | x/6+7=18 | | r-4/5=-21/4 |